A Visual Programming Framework for Wireless Sensor Networks in Smart Home Applications - Serna, Maria (2015)
In this paper, we build upon the Internet of Things (IoT) paradigm, with aim of delivering networked solutions that enable to connect not only single sensors, but also whole wireless sensor networks (WSN) to the Internet in a secure, simple and efficient way, and describe the design and implementation of a smart-home management system. The system is composed of a lightweight tool with an intuitive user interface for commissioning of IPenabled WSN with constrained capabilities. The solution includes a visual programming interface with a common framework for discovering smart home services on the constrained WSN, and a code analysis and translation engine to generate python code. This engine analyses the application rules defined with the graphical user interface and translates them into distributed application scripts. The system also includes modules to plan the optimization of the deployment, and deploy and start the generated code. A prototype of the system, with the visual programming solution and code generation module developed is presented in this paper.